Introduction to the library and information professions - Greer, Roger C. (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2013)
This comprehensive book prepares readers for a changing profession in the library and information field, presenting a holistic approach that examines theories and models and utilizes creative problem-solving strategies